Changes in Rumen Microbial Profiles and Subcutaneous Fat Composition When Feeding Extruded Flaxseed Mixed With or Before Hay - Petri, Renee M.; Vahmani, Payam; Yang, Hee Eun; Dugan, Michael E. R.; McAllister, Tim A. (Frontiers in Microbiology, 2018)
Extruded flaxseed (25%) and ground hay (75%) were each fed (DM basis) either together in a total mixed ration (TMR) or as flaxseed first followed by hay (non-TMR) to three pens of eight crossbred steers (n = 24 per diet) for 240 days. Compared to TMR, feeding non-TMR enriched subcutaneous fat with α-linolenic acid (ALA, 18:3n-3) and its biohydrogenation intermediates including vaccenic acid (trans(t)11-18:1), rumenic acid (cis(c)9,t11-conjugated linoleic acid) and conjugated linolenic acid (CLnA). Rumen microbial analysis using QIIME indicated that fourteen genera differed (P ≤ 0.05) between TMR and the non-TMR. Azoarcus and Streptococcus were the only genera which increased in relative abundance in the TMR fed steers, whereas Methanimicrococcus, Moryella, Prevotella, Succiniclasticum, Succinivibrio, Suttenella, and TG5 decreased as compared to steers fed the non-TMR. Among these, Moryella, Succiniclasticum and Succinivibrio, spp. were correlated with fatty acid profiles, specifically intermediates believed to be components of the major biohydrogenation pathway for ALA (i.e.t11,c15-18:2, c9,t11,c15-18:3, and total CLnA). In addition, negative correlations were found between the less abundant Ruminoccocus-like OTU60 and major ALA biohydrogenation intermediates, as well as positive correlations with several intermediates from alternative pathways that did not involve the formation of trans 11 double bonds. The present results suggest a number of pathways for ALA biohydrogenation are operating concurrently in the rumen, with their balance being influenced by diet and driven by less abundant species rather than members of the core bacterial population.